The Birth of Petroleum Path Dependence: Oil Narratives and Development in the North. Issue 2 (3rd April 2019) - Herrmann, Victoria
ABSTRACT: This article focuses on three moments in Alaskan history that were mediated through southern visual narratives in the 1970s: the discovery of oil; the Alaska Native Claims Settlement Act; and the construction of the Trans-Alaska Pipeline. First, the article introduces the media context of the time and the news sources used in the visual discourse analysis that follows. It offers a description of the introduction of television nightly news and discusses the sources chosen for analysis: NBC Evening News and CBS Evening News. Second, the article discusses the print photojournalism of National Geographic magazine and the New York Times. Visuals published in these outlets from 1967 through to the completion of the Trans-Alaska Pipeline in 1977 are then analyzed as discursive negotiations between Native paternalism, extermination, and self-determination for Native rights, and between environmentalism and development. The article argues that there were visual tensions between Native activists and negotiators and the strong legacies of American settler colonialism present in American reporting of 1970s Alaska. Finally, the article deconstructs the metanarrative of oil in Alaska during the 1973 oil crisis—namely, the essentiality of producing domestic oil during the 1973 oil crisis to secure the independence of the United States.